1998
DOI: 10.1271/bbb.62.2446
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Nucleotide Sequence of the Gene Encoding a Serine Proteinase Inhibitor Named Marinostatin from a Marine Bacterium,Alteromonassp. Strain B-10-31

Abstract: The gene (mstI) encoding a serine proteinase inhibitor named marinostatin from marine Alteromonas sp. strain B-10-31 was cloned and its nucleotide sequence was analyzed. A short open reading frame of 192 bp encoded 63 amino acids with a molecular weight of 6,985. Furthermore, the initial product of marinostatin (marinostatin L) was purified and its amino acid sequence was analyzed. These results indicate that marinostatin is produced as a unique precursor consisting of the mature peptide and the leader peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…As mentioned above, the Arg 5 NH of MST-2SS exchanged much faster than that of MST- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and the Cys 8 NH of MST-2SS also exchanged faster, as compared to the corresponding residue (Ser 8 ) of MST- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The undefined mutual position between the N-and C-cyclic regions of MST-2SS should cause the fast exchange of the Cys 8 residue, because the amide proton of Ser 8 in MST (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) is covered with the C-cyclic region ( Figure 5). The existence of the structural difference between MST-2SS and MST (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)…”
Section: Arg 5 H /H and Asp 9 H Rmentioning
confidence: 63%
See 4 more Smart Citations
“…As mentioned above, the Arg 5 NH of MST-2SS exchanged much faster than that of MST- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and the Cys 8 NH of MST-2SS also exchanged faster, as compared to the corresponding residue (Ser 8 ) of MST- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The undefined mutual position between the N-and C-cyclic regions of MST-2SS should cause the fast exchange of the Cys 8 residue, because the amide proton of Ser 8 in MST (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) is covered with the C-cyclic region ( Figure 5). The existence of the structural difference between MST-2SS and MST (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)…”
Section: Arg 5 H /H and Asp 9 H Rmentioning
confidence: 63%
“…Hydrogen-deuterium experiments of MST (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) showed that the backbone NH protons of Arg 5 , Tyr 6 , and Ser 8 were slowly exchanged (Figure 4): The exchange rate of Arg 5 was the slowest one, 3 × 10 -4 min -1 , and those of Tyr 6 and Ser 8 were both 2 × 10 -3 min -1 . Those exchange rates were significantly slower than those of a random coiled peptide (24).…”
Section: Arg 5 H /H and Asp 9 H Rmentioning
confidence: 99%
See 3 more Smart Citations